Provision of water supply in emergency response: Evaluation of current practices and recommendations for the future - Sikder, Abu Hena Mustafa Kamal. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Civil Engineering.; Advisor: Daniele Lantagne.; Committee: Elena Naumova, David Gute, Thomas Handzel, and David Tsetse.; Keyword: Environmental health.